POPULATION CONTROL POLICIES IN THE SPECIAL REGION OF YOGYAKARTA AFTER TOTAL FERTILITY RATE INCREASED BASED ON IDHS 2017 - Muhammad Arif Fahrudin Alfana; Agus Joko Pitoyo; Rizky Laudiansyah; Sri Sugiharti (Yogyakarta State University, 2020)
This study has two main objectives. The first is to explain the achievement of the value of Total Fertility Rate (TFR) in the Special Region of Yogyakarta (DIY). The second is to explain the population control policy after the increase in TFR in DIY results of the 2017 IDHS. The population control policy taken by the DIY government comes from the Grand Design of Population Development document published by the People's Welfare Bureau. The method used in this study is library research. The analyst uses qualitative descriptive. The results showed that according to IDHS data, there had been fluctuations in the value of TFR during 1991-2017. In the last ten years, the pattern of TFR values in DIY has tended to increase. Population control is necessary to prevent this tendency. The policies taken by the government in the future in terms of population control in DIY include suppressing population growth rates, maturing marital age, controlling the value of TFR, and increasing the prevalence of contraception. The DIY government will implement at least this policy until 2035.